2015
DOI: 10.1096/fj.15-279588
|View full text |Cite
|
Sign up to set email alerts
|

The toll of the gridiron: damage‐associated molecular patterns and hypertension in American football

Abstract: American football has unequivocally been linked to elevations in blood pressure and hypertension, especially in linemen. However, the mechanisms of this increase cannot be attributed solely to increased body weight and associated cardiometabolic risk factors (e.g., dyslipidemia or hyperglycemia). Therefore, understanding the etiology of football-associated hypertension is essential for improving the quality of life in this mostly young population, as well as for lowering the potential for chronic disease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…TLR-4, which is expressed on monocytes [68], has been shown to induce NET formation [63]. Apart from lipopolysaccharide, TLR-4 recognizes a variety of danger-associated molecular patterns, including high mobility group box 1 (HMGB1) [65], which is a component and important inducer of NETs [40, 42]. Addition of an anti-TLR-4 blocking antibody exerted a similarly inhibitory effect as DNase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TLR-4, which is expressed on monocytes [68], has been shown to induce NET formation [63]. Apart from lipopolysaccharide, TLR-4 recognizes a variety of danger-associated molecular patterns, including high mobility group box 1 (HMGB1) [65], which is a component and important inducer of NETs [40, 42]. Addition of an anti-TLR-4 blocking antibody exerted a similarly inhibitory effect as DNase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have confirmed a similar increase in heart disease mortality in active and former ASF linemen as well as a higher risk of metabolic syndrome and subclinical carotid atherosclerosis (11,29,30). While elevated body mass has been proposed as a key explanatory factor, this parameter unlikely explains the complete mechanistic story (10,31). Data from the current study introduce a more comprehensive mechanistic explanation in the form of acquired, early-life hypertension with resultant target organ damage in the form of concentric LV hypertrophy with subclinical LV systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes causes increased serum levels of high mobility group-B1 (HMGB1) [60] , a known DAMP [31] that activates TLR4 [31] , which would be expected to enhance inflammation. Similarly, in some cases hypertension has also been proposed to result from enhanced serum DAMP levels (reviewed in [61] ), which again could possibly lead to a chronic low-level inflammation. Obesity is also thought to be accompanied by inflammation (reviewed in [62] ).…”
Section: Additional Considerationsmentioning
confidence: 99%